CHANGE IN THE FUNCTIONAL STATE OF ERYTHROCYTES AS A COMPONENT OF MICROCIRCULATORY DISORDERS IN METABOLIC SYNDROME - V. I. Podzolkov; T. V. Koroleva; A. Е. Bragina; M. G. Kudryavtseva; N. A. Druzhinina; M. V. Pisarev (Рациональная фармакотерапия в кардиологии, 2018)
Aim. To study the erythrocyte electric charge (EEC) in patients with metabolic syndrome (MS) depending on glycemia levels. Material and methods. 112 patients (45 men and 67 women, age 61.4Ѓ}7.2 years) with MS (MS duration 8.7Ѓ}5.2 years) were studied. EEC level was detected by the method of adsorption of a positive cationic dye (cationic blue O) on the surface of the erythrocyte plasma membrane up to the complete neutralization of their negative charge, followed by photometry of the solution and calculation of the number of charges on the erythrocyte cell surface. All statistical analyses were done using Statistics 10.0 software.Results: Abdominal obesity was registered in 100% of patients, hypertension – in 73%, fasting hyperglycemia – in 75%, dyslipidemia – in 80% of patients. Mean glycated hemoglobin (HbA1c) level in patients with MS was 7.3Ѓ}1.9%. The mean EEC level in group of MS patients (1.59Ѓ}0.05×107) was significantly lower than in the control group (1.67Ѓ}0.03×107), p<0.05. In patients with MS and fasting hyperglycemia the EEC levels were significantly lower than in those without fasting hyperglycemia (1.58Ѓ}0.05×107 vs 1.64Ѓ}0.03×107, respectively, p<0.001). Significant negative correlations between EEC and age (r=-0.43, p<0.05), average duration of MS (r=-0.87, p<0.05), average plasma glucose concentration (r=-0.6, p<0.05), average duration of fasting hyperglycemia (r=-0.83, p<0.05), and blood HbA1c level (r=-0.56, p<0.05) were found in patients with MS.Conclusion: Significantly lower values of EEC are observed in MS patients with increasing age, duration of MS, and duration of hyperglycemia. Negative correlation between HbA1c and EEC was also shown.